A typology of e-governance operational Information Systems tasks. (9th November 2009) - Prasad, Sameer; Jasmine, Tata; Dougan, William; Munro, David
In this research a typology of Information Systems (IS) tasks is developed based on existing dimensions reported earlier in the literature. This typology allows one to classify not only the traditional e-governance IS, but also lay the foundations for technologies/methods yet to be developed. It also provides a prescriptive element in designing current and future e-governance information systems. The resulting framework also provides one approach for government officials in accessing and managing the risk associated with developing, implementing and managing future e-governance projects.